2003
DOI: 10.1519/1533-4287(2003)017<0342:eoashw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Submaximal Half-Squats Warm-up Program on Vertical Jumping Ability

Abstract: The purpose of the current research was to study the effect of a warm-up program including submaximal half-squats on vertical jumping ability. Twenty physically active men participated in the study. Each subject performed 5 sets of half-squats with 2 repetitions at each of the following intensities: 20, 40, 60, 80, and 90% of the 1 repetition maximum (1RM) load. Prior to the first set and immediately after the end of the last set, the subjects performed 2 countermovement jumps on a Kistler force platform; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
143
1
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(173 citation statements)
references
References 0 publications
15
143
1
14
Order By: Relevance
“…Evidence suggests that PAP may enhance the ability of muscle to produce more force at a faster rate following previous muscle contractions. Over the past decade research has focussed on the effects of PAP on athletic performance using dynamic movements (1,8,13,16,21,24) and isometric maximum voluntary contractions (6,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that PAP may enhance the ability of muscle to produce more force at a faster rate following previous muscle contractions. Over the past decade research has focussed on the effects of PAP on athletic performance using dynamic movements (1,8,13,16,21,24) and isometric maximum voluntary contractions (6,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers (Gullich and Schmidtbleicher, 1996;Gourgoulis et al, 2003;Young et al, 1998) reported that warm-ups of maximal isometric contraction and maximal or high-intensity dynamic exercise can enhance dynamic muscle performances such as jump height. The disagreement of our study and the above previous studies may be due to differences in the following two points.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing muscle temperature results in improved muscle function and resilience of soft tissues (Yamamoto and Yamamoto, 1993). Previous studies have clarified that prior maximal voluntary isometric contractions (Gullich and Schmidtbleicher, 1996) and submaximal high-intensity contractions (2 repetitions of 20-90% of the 1 repetition maximum (1RM) load (Gourgoulis et al, 2003), 5 repetitions of 5RM intensity (Young et al, 1998)) can increase the rate of force development and jump height during repeated countermovement jumps and drop jumps (Gullich and Schmidtbleicher, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the research on CT utilized a protocol involving a strength exercise followed by a power exercise [1,3,[6][7][8][9][10][11][12]. However, few studies have been conducted using an initial power exercise instead of the more often used strength exercise in the complex pair [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the KSJ group, four to six repetitions of kettlebell swings were performed followed by five consecutive countermovement squat jumps. A recovery period of 3 min between the resistance training exercise (squats/ kettlebell swings) and the plyometric exercise (countermovement squat jumps) was provided to allow for phosphocreatine resynthesis [7,9,19,20] (Figure 4).…”
mentioning
confidence: 99%